Torsi Balok Baja Berprofil I Berpengaku Vertikal - Tudjono, Sri (MEDIA KOMUNIKASI TEKNIK SIPIL, 2006)
Vertical stiffeners are usually used to resist shear force or to stiffen web plate in accordance with local buckling. Vertical stiffeners which have torsional stiffness can disturb warping of the beam. So the vertical stiffeners can increase the torsional stiffness of the beam. The relation between the torsion of vertical stiffener to warping of the beam must firstly be found. By the boundary conditions of the beam at the two ends and at the vertical stiffeners, all integration constants of diferential equation of each field rotation can be found. Analysis can be done on various thickness and various numbers of vertical stiffeners. It can be concluded that the increase of torsional stiffness caused by the increase of the of vertical stiffener thicknessÂ  are significant. The gradient of the torsional stiffness increase tend relatively smaller at the greater number of vertical stiffeners.Keywords: vertical stiffener, warping, torsionPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3942[How to cite: Tudjono, S., 2006, Torsi Balok Baja Berprofil I Berpengaku Vertikal, Jurnal Media Komunikasi Teknik Sipil, Volume 14, Nomor 2, pp. 150-155]